Annual flood-layer thickness of sediment core POS362-2_33 - Blanchet, Cécile L; Ramisch, Arne; Tjallingii, Rik; Ionita, Monica; Laruelle, Louison; Meike, Bagge; Klemann, Volker; Brauer, Achim (PANGAEA, 2024)
The dataset provides a continuous record of layer thickness for sediments deposited during annual floods of the Nile River during the North African Humid Period (ca. 9.5-7.5 ka BP). The study site is located on the Nile deep-sea fan, where marine sediment core POS362_2_33 was collected in 2008. After subsampling the core, sediment blocks were embedded in resin and thin sections were cut. Layer identification, counting and thickness measurement were realised under the microscope. We provide here the raw flood-layer thickness as well as normalised (log-scale), detrended (differentiated) and filtered data on the depth and age scales. Further details can be found in the related manuscripts.
Keywords: flood frequency; Green Sahara; Nile River; Varve